Measuring Work Related Quality of Life and Affective Well-being in Turkey - Duyan, Emin Cihan; AytaÃ§, Serpil; Akyildiz, Neslihan; Laar, Darren Van (Richtmann Publishing, 2013)
The prime purpose of this research wass to test the cross cultural construct validity and the reliability of the Work RelatedQuality of Life (WRQoL) scale developed by Van Laar and colleagues (2007) and Job Related Affective Well-being Scale bySevastos (1996). 288 employees participated in the study from a range different occupational backgrounds. The employeeshad a mean age of 34.25 years and average work experience of 12.17 years. 52.1% of the participants were men. Three itemsneeded to be removed from WRQoL according to the CFA results and the new structure for Turkish version of the WRQoLconsisted of 20 items and 6 factors with acceptable to good fit indices. Job related affective well-being scale showed aconsistent factor and item structure with the Turkish sample indicated by good fit indices. All sub-scales and scales showedsignificant correlations. We might consider that the 20 item WRQoL and 12 item job related affective well-being scae are bothvalid and reliable in a Turkish context.